The effectiveness of compassion focused therapy with clinical populations: A systematic review and meta-analysis - Millard, L.A.; Wan, M.W.; Smith, D.M.; Wittkowski, A. (Journal of affective disorders, 2023)
Over the last 20 years, compassion focused therapy (CFT) has gained popularity as an emerging ‘third wave’ intervention. Although previous reviews indicated its potential benefits, a systematic review and meta-analysis of CFT in those with mental health difficulties has yet to be conducted. A systematic search of five databases was undertaken, focusing on randomised controlled trials and randomised pilot/feasibility studies of CFT only. No language restrictions were implemented. A narrative synthesis was conducted. Random effects meta-analyses were measured on levels of self-compassion, self-criticism/self-reassurance, fears of compassion and clinical symptomology. Fifteen studies from 2013 to 2022 were included. Findings suggested that CFT was effective in improving compassion-based outcomes and clinical symptomology from baseline to post-intervention and compared to waitlist control. A range of small to large effect sizes were reported for improvements in self-compassion (0.19–0.90), self-criticism (0.15–0.72), self-reassurance (0.43–0.81), fear of self-compassion (0.18), depression (0.24–0.25) and eating disorders (0.18–0.79). Meta-analyses favoured CFT in improving levels of self-compassion and self-reassurance than control groups. The methodological quality of many of the included studies (7/15) was rated as ‘unclear’ due to a lack of information. There was a distinct gender gap, with 74.88% identifying as female participants. This review was the first to examine the effectiveness of CFT in clinical populations. The results indicate that CFT has promising clinical implications, suggesting that the intervention increases compassion-based outcomes and reduces clinical symptomology in those with mental health difficulties. However, future research is required into the long-term effects of CFT. •CFT improved clinical symptomology from baseline to post-intervention.•CFT revealed to be effective across outcomes, compared to controls.•Meta-analysis significantly favoured CFT in increasing self-compassion.•Meta-analysis significantly favoured CFT in improving levels of self-reassurance.